Multi-scale hydrological system-of-systems realized through WHOS: the brokering framework - Enrico Boldrini; Stefano Nativi; Silvano Pecora; Igor Chernov; Paolo Mazzetti (International Journal of Digital Earth, 2022)
Global Change challenges are now systematically recognized and tackled in a growingly coordinated manner by intergovernmental organizations such as the United Nations. Heterogeneous observing networks provide the founded data sources to assess the Earth environmental status and take sound decisions to achieve a sustainable development. WMO Hydrological Observing System (WHOS) allows to discover and access historical and near real time hydrological observations. WHOS represents the hydrological contribution to the wider WIGOS-WIS system of WMO. It is a digital ecosystems framework contributed by a set of data providers and technical support centers. In this framework, three regional pilots were successfully completed. The WHOS architecture applies the services brokering style, implemented through the Discovery and Access Broker technology. A brokering approach makes a global system of systems possible and sustainable, where the different enterprise systems are enabled to interoperate, despite they implement heterogeneous communication interfaces and data models. In this manuscript, the WHOS brokering solution is detailed by recurring to the definition of a set of transversal viewpoints to describe the important aspects of the complex ecosystem –namely: enterprise, information, computational, engineering, and technological views. Finally, the three regional pilot ecosystems are described as successful cases of WHOS implementation.